Fundoscopy screening for intraocular candida in patients with positive blood cultures—is it justified?. (November 2018) - El-Abiary, Mariam; Jones, Brian; Williams, Graeme; Lockington, David
Abstract Introduction Although the worldwide prevalence of disseminated candidaemia is rising, reported intraocular candidiasis rates are variable, even as low as 1%. The Infectious Diseases Society of America recommends fundoscopy screening for all fungal blood culture positive patients. We wished to evaluate the impact of this recommendation on our department. Methods A retrospective observational study was performed in NHS Greater Glasgow and Clyde (population = 1.15 million) for all patients with candida positive blood culture results over a 2-year period. Results From January 2015 to December 2016, 258 candida positive cultures were obtained from 168 adults (mean age = 62 years, range: 17–94 years; 85 females, 83 males). Candida species were isolated in 161/168 (95.8%) cases (43.5%Candida albicans, 35.7%Candida glabrata ). All 168 cases were treated with intravenous antifungals. 84 patients (50%) were formally referred to ophthalmology. Of those not referred, 21 were deceased prior to culture result (12.5%) and 14 patients subsequently deteriorated (8.3%). Six patients reported visual symptoms. In total, 65% had no ocular findings and 32.5% had unrelated ocular signs. Only one patient had signs consistent withCandida chorioretinitis, making the prevalence of intraocular candida in our population 1.3% (1/80). Conclusions The prevalence of ocular candidiasis is low, presumably due to potent systemic antifungal agents and good intraocular penetration. Our findings support the view that routine fundoscopy screening may not be indicated in every culture positive patient. This paper provides an evidence base for the Royal College's Eyecare in intensive care unit recommendations regarding targeted screening of non-verbal, symptomatic or high-risk patients.